Road Capacity, Domestic Trade and Regional Outcomes - Cosar, A. Kerem; Demir, Banu; Ghose, Devaki; Young, Nathaniel (World Bank, Washington, DC, 2021)
What is the impact on intranational trade and regional economic outcomes when the quality and lane capacity of an existing paved road network is expanded significantly? This paper investigates this question for the case of Turkey, which undertook a large-scale public investment in roads during the 2000s. Using spatially disaggregated data on road upgrades and domestic transactions, the paper estimates a large positive impact of reduced travel times on trade as well as local manufacturing employment and wages. A quantitative exercise using a workhorse model of spatial equilibrium implies heterogeneous effects across locations, with aggregate real income gains reaching 2–3 percent in the long run. Reductions in travel times increased the local employment-to-population ratio but had no effect on local population. The model is extended by endogenizing the labor supply decision to capture this finding. The model-implied elasticity of employment rates to travel time reductions captures about one-third of the empirical elasticity.